Unusual Variant of Unicystic Ameloblastoma with CEOT-Like Areas: A Rare Case Report with Review of Literature - Venkata Ramanand Oruganti; Shylaja Sanjeevareddygari; Manay Srinivas Munisekhar; Sharath Kumar Reddy Eppalapalli; Raghu Vamshi Vishwakarma; Kiran Kumar Ganji; Kiran R. Halkai; Rahul Halkai (Hindawi Limited, 2021)
Ameloblastoma is an epithelial odontogenic neoplasm with clinical and histological diversity. They are locally invasive tumors with 3 clinical variants such as solid, unicystic, and peripheral ameloblastomas, and the unicystic variant constitutes only 13%. Histologically, it shows diverse microscopic patterns that may occur isolated or in combination with other patterns. The granular cell variant accounts for 3.5% of all ameloblastoma cases. The eosinophilic granules seen in the cytoplasm of the tumor are thought to be lysosomes and presumably contribute to the pathogenesis of the tumor. Although such a phenomenon is rare in unicystic ameloblastoma, granular cell differentiation in solid multicystic ameloblastoma is a well-established phenomenon. In this paper, we present a unique case of unicystic ameloblastoma with granular cell differentiation with a brief review.